Re-living liberation war militia bases: violence, history and the making of political subjectivies in Zimbabwe - Chitukutuku, Edmore (My University, 2017)
In this study, I explore the ways in which legacies of how and where the Zimbabwean liberation war was fought, the landscapes of the struggle, and the violence associated with it were invoked at district and village level by ZANU PF as it sought to instill loyalty, fear and discipline through its supporters and the youth militia. Although they were invoking memories of former guerrilla bases, and the violence often associated with them, the bases set up by ZANU-PF youth militia in 2008 were not established on the actual sites of former guerrilla camps. However, since then, ZANU-PF war veterans in the Zimbabwe National Army (ZNA) have been returning to the actual sites of the 1970s liberation war guerrilla bases in order to teach senior staff the history of the liberation struggle, drawing together former liberation war collaborators or ‘messengers’ who assisted guerrilla fighters during the war, as well as contemporary unemployed ZANU-PF youth. They used these often highly choreographed events to talk about battles during war, to perform liberation songs, and to explain how ancestors assisted them during the struggle. I examine these recent events, and argue that both the establishment of the new militia bases in the post-2000 period, and invocation of the old, former guerrilla bases dating to the Chimurenga period are deliberate efforts by ZANU-PF to make violence, geography and landscapes do political/ideological work by forging political subjectivities and loyalties that sustain its rule. In stressing these continuities between the 1970s guerrilla bases, and their invocation and reproduction in post-2000 Zimbabwe, I am interested in what the base enables and does in terms of the formation of political subjectivities. I aim to show through critical analysis of the political history and local accounts of the second Chimurenga why political subjectivity and the base are important in the re-examination of both the history and the literature on this history. The base allows for a sophisticated reading of political subjectivity in that it was the space through which the grand narrative of the liberation struggle hit the ground, entered into people’s homes, and constituted a complex relationship between political education, conscientisation, freedom and violence. The liberation war base was meant to make people inhabit subjectivities characterized by bravery, resistance, and resilience when fighting the might of Rhodesian army. In the post-colonial context, the base served the purpose of annihilating the kind of rebellious subjectivities inhabited during the liberation war and replacing them with those characterized by fear, pretense, and quietude. This substitution explains the subjectivities that exist in the post-independence rural population and reveals the purpose that electoral violence has served in Zimbabwe’s post-independence period, especially through the base. However people have also engaged with these landscapes outside of ZANU-PF politicking and this has produced critical subjectivities where people challenge ZANU-PF dominant narratives.
Thesis submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy (Anthropology), March 2017
Keywords: ZANU-PF (Organization--Zimbabwe); National liberation movements--Zimbabwe--History; Political participation--Zimbabwe; Zimbabwe--Politics and government.